2020
DOI: 10.3390/joitmc6040185
|View full text |Cite
|
Sign up to set email alerts
|

Productization of Industrial Side Streams into By-Products—Case: Fiber Sludge from Pulp and Paper Industry

Abstract: The increasing pressure on natural resources and the climate has been noted by businesses and governments worldwide, who now face the difficult task of integrating paths of environmental sustainability and economic growth. One promising approach to sustainable development, reducing the pressure on natural resources and solving waste problems is circular economy. From different ways of implementing circular economy, this study focuses on the productization of industrial side streams, which carry a great deal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…However, the company has encountered challenges related to reverse logistics, including freight costs, custom fees, delays and fiscal issues, as recognised also by [8,10,18]. Collecting the cores from customers is also difficult, which is in line with the findings of [1,22]. The deposit system has been seen as a solution to prevent unauthorised remanufacturing and return the cores more efficiently from the customers.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the company has encountered challenges related to reverse logistics, including freight costs, custom fees, delays and fiscal issues, as recognised also by [8,10,18]. Collecting the cores from customers is also difficult, which is in line with the findings of [1,22]. The deposit system has been seen as a solution to prevent unauthorised remanufacturing and return the cores more efficiently from the customers.…”
Section: Discussionmentioning
confidence: 95%
“…This should be taken into account in the design phase to consider all life-cycle phases [28]. As many authors have concluded [6,22], excessive generated emissions or excessive amounts of used energy in reverse logistics or other circular economy processes may reduce the environmental benefits of the circular economy systems. However, the value chain of manufacturing itself generates significant emissions and requires the use of energy in various phases; thus, it is easy to see why remanufacturing can be perceived as a green solution despite having various challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Service productisation provides a common language for stakeholders (Wirtz, 2021). All involved parties can have a clearer understanding of the offering (Lepp€ anen et al, 2020). The service elements being described, the company internally supports employees and others relating to the services (Danson et al, 2005;Harkonen et al, 2017;Simula et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The service product portfolio management is improved through service productisation (Saunila et al, 2017). Productisation enables a better position to address the overall offering (Wirtz, 2021;Lepp€ anen et al, 2020). In addition, productisation inducing the human ability to evaluate and relate to ongoing actions, structures and their own roles have been mentioned (Lehtonen et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%